2021
DOI: 10.1021/acs.chemmater.1c01054
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Ru for Replacing Cu-Interconnects

Abstract: The atomic layer deposition (ALD) of Ru using a metal–organic precursor, tricarbonyl­(trimethylenemethane)ruthenium [Ru­(TMM)­(CO)3] and O2 as a reactant is reported. The high vapor pressure, thermal stability, and relatively small ligands of the precursor facilitate efficient ALD. Typical self-limiting growth and an ALD temperature window of 220–260 °C are observed along with significantly high growth per cycle (GPC) (∼1.7 Å) and short incubation cycles (∼6) at 220 °C. Density functional theory calculations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 84 publications
2
28
0
Order By: Relevance
“…It is often observed that nucleation during ALD is enhanced on catalytic substrates such as Ru. 44,71,72 For either mechanism on Ru, the calculated adsorption energy of the TICP precursor is highly exothermic. The reaction energies of the two reactions on Ru can be summarized as follows A thin Ir film was deposited on a nanoscale 3D structure with a SiO 2 surface to confirm the conformability of our TICP process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is often observed that nucleation during ALD is enhanced on catalytic substrates such as Ru. 44,71,72 For either mechanism on Ru, the calculated adsorption energy of the TICP precursor is highly exothermic. The reaction energies of the two reactions on Ru can be summarized as follows A thin Ir film was deposited on a nanoscale 3D structure with a SiO 2 surface to confirm the conformability of our TICP process.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the surface-dependent growth of Ir by ALD, a Ru thin film was introduced as the seed layer for rapid Ir nucleation. First, the Ru layer was deposited by ALD 44 on a dual-trench structure (top and bottom openings: ∼40 and ∼15 nm, respectively) with an average aspect ratio of ∼6.3. Ru ALD showed no nucleation delay on the SiO 2 substrate, at a deposition temperature of 260 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…the current density that induces failure at 10 y. Under such a scenario, interconnects based on Ru and Co are potential replacements with better reliability than Cu because of their lower resistivity and higher EM activation energies [55][56][57][58][59][60]. The barrierless Ru interconnect together with an integration scheme have been identified to be more EM reliable than Cu [61].…”
Section: Model Applicationsmentioning
confidence: 99%